Electrodeposition of photoactive 1D gallium selenide quantum dots - Gujar, T. P.; Shinde, V. R.; Park, Jong-Won; Lee, Hyun Kyung; Jung, Kwang-Deog; Joo, Oh- Shim (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
One-dimensional (1D) quantum dots of gallium selenide have been obtained by cathodic electrodeposition onto the tin doped indium oxide (ITO) glass substrates from aqueous acidic solutions at room temperature. Characterizations of the as-deposited films by energy dispersive X-ray (EDX) spectroscopy confirm a selenium rich chemistry, X-ray diffraction (XRD) shows that mixture of phases like GaSe/Ga2Se3, and optical spectroscopy shows a direct optical band gap of 2.85 eV with intermediate transition energy at 1.9 eV. From transmission electron microscopy (TEM), the films show the one-dimensional quantum dots chains in grains. Scanning electron microscopy (SEM) images indicate dimorphous placement of nanoparticles. The elementals surface analysis of the core-shell nanoparticles determined by X-ray photoelectron spectroscopy (XPS) supported the EDX results and confirmed the chemical nature of the material. The photoelectrochemical (PEC) studies of gallium selenide films were carried out and the nanocrystalline gallium selenide films were found to be photoactive in aqueous sodium thiosulphate solution. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: MOLECULAR-BEAM EPITAXY; THIN-FILMS; GA2SE3 FILMS; GROWTH; DEPOSITION; SEMICONDUCTORS; PHASE